Bài giảng theory of translation - Huỳnh, Trung Tín (Trường Đại học Cần Thơ, 2000)
This theorry includes many lessons: the nature of meaning, linguistic meaning, referential meaning, the dynamic dimension in communication, equivalence at word level, types of correspondences and contrasts, techniques of adjustment.